PEMANFAATAN TUMBUHAN OBAT OLEH MASYARAKAT DESA TOLIWANG KECAMATAN KAO BARAT KABUPATEN HALMAHERA UTARA - Filadelfia Moumou; Alfonsius A. Thomas; Reynold P. Kainde; Wawan Nurmawan (COCOS, 2015)
ABSTRACT The traditional use of medicinal plants has been practiced throughout history and passed down through the generations. This research focuses on the use of medicinal plants for traditional treatments in Toliwang village. Data was collected through questionnaires. Respondents are traditional healers (Battra) and based on local names, 14 species of medicinal plants were identified. After identification, red leleko and white leleko was concluded as the same species, resulting in a final count of 13 species distributed across 9 families, which included 8 shrub, 4 trees, and 2 lianas that are used to treat 9 different illnesses. Keywords: Plant, medicine, traditional, species, perdu, tree, liana.